2016
DOI: 10.21037/jtd.2016.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of programmed cell death ligand 1 (PD-L1) expression in patients with esophageal squamous cell carcinoma: a meta-analysis

Abstract: Based on the published studies, PD-L1 overexpression in ESCC was not associated with common clinicopathological characteristics. PD-L1 might be a poor prognostic biomarker for ESCC. Further large-scale research should be performed to reveal the precise clinicopathological and prognostic significance of PD-L1 in ESCC by unified testing standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Qu et al [ 97 ] performed a meta-analysis of the prognostic significance of PD-L1 expression in ESCC patients. The study showed that overexpression of PD-L1 tended to be associated with short OS in ESCC; however, the difference did not reach statistical significance ( P = 0.07).…”
Section: Resultsmentioning
confidence: 99%
“…Qu et al [ 97 ] performed a meta-analysis of the prognostic significance of PD-L1 expression in ESCC patients. The study showed that overexpression of PD-L1 tended to be associated with short OS in ESCC; however, the difference did not reach statistical significance ( P = 0.07).…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 40 ] However, inconsistent results have been reported in esophageal squamous cell cancer, and head and neck cancer, with no association between PD-L1 expression and survival. [ 41 , 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted to evaluate the association of clinical parameters with expression of various proteins in ESCC by immunohistochemistry . Despite aggressive attempts at identifying tumor markers specific to esophageal cancer, no definitive marker has been identified that can be used universally to monitor tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%